2021
DOI: 10.1063/5.0054665
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based study on water radiolysis species for 1H+, 4He2+, and 12C6+ ion beams with multiple ionization using Geant4-DNA

Abstract: Monte Carlo track structure simulation is a powerful method for estimating damage induced by water radiolysis products for cell killing. To investigate the influence of multiple ionization for the formation of water radiolysis products under 1 H + , 4 He 2+ , and 12 C 6+ ion beams, a Monte Carlo simulation based on Geant4-DNA was carried out. The G-value of H 2 O 2 increased monotonically with increasing linear energy transfer up to 200 eV/nm. Above 200 eV/nm, the G-value of H 2 O 2 began dropping, but only wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, discrepancies between simulated yields of H 2 O 2 and experimental yields have been attributed to the fact that multiple ionizations of the same water molecule have no process in Geant4‐DNA. It was found that at high LET there was a reduction in the yield of H 2 O 2 due to these multiple ionizations 72 . The available H 2 O 2 is also implicated in the Fenton reaction, given by H2O2+Fe2+·OH+OH+Fe3+$$\smash{${\mathrm{H}}_{2}{\mathrm{O}}_{2}+{\mathrm{Fe}}^{2+}\to {}^{\cdot}\mathrm{OH}+{\mathrm{OH}}^{-}+{\mathrm{Fe}}^{3+}$}$$ which, at the time the simulations were ran, could not be included due to the lack of appropriate chemical species, as well as time scale limitations in TOPAS‐nBio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, discrepancies between simulated yields of H 2 O 2 and experimental yields have been attributed to the fact that multiple ionizations of the same water molecule have no process in Geant4‐DNA. It was found that at high LET there was a reduction in the yield of H 2 O 2 due to these multiple ionizations 72 . The available H 2 O 2 is also implicated in the Fenton reaction, given by H2O2+Fe2+·OH+OH+Fe3+$$\smash{${\mathrm{H}}_{2}{\mathrm{O}}_{2}+{\mathrm{Fe}}^{2+}\to {}^{\cdot}\mathrm{OH}+{\mathrm{OH}}^{-}+{\mathrm{Fe}}^{3+}$}$$ which, at the time the simulations were ran, could not be included due to the lack of appropriate chemical species, as well as time scale limitations in TOPAS‐nBio.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that at high LET there was a reduction in the yield of H 2 O 2 due to these multiple ionizations. 72 The available H 2 O 2 is also implicated in the Fenton reaction, given by H 2 O 2 + Fe 2+ → ⋅ OH + OH − + Fe 3+ which, at the time the simulations were ran, could not be included due to the lack of appropriate chemical species, as well as time scale limitations in TOPAS-nBio. It's importance lies not only in the modification of the yield of H 2 O 2 , but also in the fact that the potential high levels of H 2 O 2 in the MB peaks may catalyze this reaction, thereby producing cytotoxic ⋅ OH.…”
Section: Discussionmentioning
confidence: 99%
“…While our results and fits are so far only valid for low LET irradiation modalities, temperaturedependence will be further expanded to include higher LET modalities in future studies. For higher LET, the number of reactions must be expanded in order to properly simulate the radiolysis of pure liquid water (Baba et al 2021a, Baba et al 2021b, Hervé du Penhoat et al 2001 and a revision to the water dissociation schemes could be necessary due to the higher contribution of oxygen reactions (Shin et al 2021). The results obtained from this and past works (D-Kondo et al 2021, Ramos-Mendez et al 2021) show that at low LET modalities, there is no need to simulate oxygen related reactions due to the low contribution that this chemical specie gives to the whole chemical yields.…”
Section: Discussionmentioning
confidence: 99%
“…Additional calculations included the energies, positions, and directions of the secondary electrons, as well as the transport of the secondary electrons. Multiple ionizations were not included [ 37 ]. The code was previously validated with experimental data such as radial dose experiments [ 38 ].…”
Section: Methodsmentioning
confidence: 99%